Pustakawan Kreatif: Mengemas Informasi Inovatif Berbasis Teknologi Informasi di Perpustakaan Universitas Muhammadiyah Sumatera Utara - Nurhumairoh, Siti; Batubara, Abdul Karim (Program Studi Teknik Informatika Universitas Pamulang, 2023)
The rapid development of technology and science has brought the phenomenon of shifting the orientation of user needs for information technology-based information For this reason, it is necessary to innovate based on the needs of information users. In the library environment of the University of Muhammadiyah North Sumatra (UMSU), librarians have an important role as creative agents in packaging innovative information based on information technology. Librarians must reflect their role as a creative profession in packaging information and show a focus on using information technology as a foundation for innovation. Therefore, in this case, researchers are interested in examining how the role of UMSU Librarians in providing benefits from librarian creativity to develop innovative strategies in packaging information to suit users and technological developments. The method used in this study is a qualitative method that uses data collection techniques through observation, interviews and documentation. Based on the research that has been done, librarians have carried out 3 creativity that produce innovative information based on information technology at the UMSU Library. For this reason, information packaging strategies are important so that users can feel a significant improvement and in accordance with the development of science and technology that exists today. The results showed that UPT Library UMSU in its information technology-based product packaging strategy had determined the target in advance, but it had not been planned properly. So the results have not been as expected. Based on the results of the research analysis that has been conducted, it is concluded that the information technology-based product packaging strategy carried out at UPT Library UMSU including digital libraries, e-journals, and online catalogs has not been utilized optimally and has not met user desires. This is due to several factors, namely content, context, and infrastructure. UPT Library UMSU has not made a strategy plan, even though the planning function is the basic foundation of the overall management function.